2017
DOI: 10.1002/phar.1965
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Monitoring Unbound Valproic Acid Concentration in Patients with Hypoalbuminemia

Abstract: This study showed that in the presence of hypoalbuminemia, high unbound VPA concentrations can be observed despite normal or low total VPA concentrations. It also demonstrated that high unbound VPA concentrations are associated with clinically significant neurologic adverse symptoms. Clinicians should be aware that unbound VPA concentration monitoring may be required in the presence of hypoalbuminemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
1
34
0
2
Order By: Relevance
“…High levels of free concentration are associated with higher risk of toxicity. 12,41 Because of the variability of unbound concentration, limitations in the interpretation of total serum concentration are expected, with potential discordance between total and free concentration. 14,41 Quantifying free concentration might be relevant in some patients, for example, in cases of suspicion of toxicity, polytherapy, hypoalbuminemia, or renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of free concentration are associated with higher risk of toxicity. 12,41 Because of the variability of unbound concentration, limitations in the interpretation of total serum concentration are expected, with potential discordance between total and free concentration. 14,41 Quantifying free concentration might be relevant in some patients, for example, in cases of suspicion of toxicity, polytherapy, hypoalbuminemia, or renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…14,41 Quantifying free concentration might be relevant in some patients, for example, in cases of suspicion of toxicity, polytherapy, hypoalbuminemia, or renal failure. 12 Because serum albumin concentration increases with age in children 42 and unbound concentration of valproate correlates with albumin concentration, 12 we could expect valproate free concentration to vary according to age. Nevertheless, no relationship between age and unbound valproate concentration has been reported in the literature yet, 43 and the decrease of clearance with increasing age seems to be mostly because of maturational changes in hepatic metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VPA also modulates neurotransmitters such as dopamine, serotonin, and voltage-gated ion channels such as sodium, calcium, and potassium channels that stabilize neuronal membranes [2]. Concerning pharmacokinetics, VPA typically has high bioavailability (90%), and albumin binding is commonly reported at 90%, but it may be much less than this in specific situations, including in low albumin states, with elevated blood urea nitrogen (BUN), and with medications that compete for binding such as lipid emulsion agents, aspirin, and phenytoin [3][4][5][6]. VPA is extensively metabolized by the liver through glucuronidation (50%), mitochondrial β-oxidation (40%), and other pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that monitoring the total valproic acid concentration can be misleading, because it can be normal or even low despite high concentrations of free valproic acid (11). If dosages are adjusted on the basis of total valproic acid levels, patients who are hypoalbuminemic can be overdosed, leading to clinically significant neurologic symptoms or toxicity (10,15). Thus, there is greater clinical utility and importance in monitoring the free valproic acid concentration, rather than the total, in patients with hypoalbuminemia (3,4,11).…”
Section: Valproic Acid Toxicitymentioning
confidence: 99%